2022
DOI: 10.1108/jilt-05-2022-0002
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents of IoT adoption in food supply chain quality management: an integrative model

Abstract: PurposeThe introduction of quality management Internet of things (QM IoT) can help food supply chain members to enhance real-time visibility, quality, safety and efficiency of products and processes. Current literature indicates three main research gaps, including a lack of studies in QM IoT in the food supply chain, the vagueness of integrative adoption of new technology framework and deficient research covering both adoption attitude and intention in the same model. This study aims to propose an analysis mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 84 publications
(361 reference statements)
2
7
0
Order By: Relevance
“…In case of trialability, the findings have indicated that this is an advantageous practice for users to trial either with limited or all functions. The participants in this study as well as researchers from prior studies [e.g., 143,144] have strongly recommended this practice. They have suggested that this characteristic affects the adoption of cloud ERP systems due to an organization being able to test the performance before adopting and deciding to purchase the system.…”
Section: Discussionmentioning
confidence: 99%
“…In case of trialability, the findings have indicated that this is an advantageous practice for users to trial either with limited or all functions. The participants in this study as well as researchers from prior studies [e.g., 143,144] have strongly recommended this practice. They have suggested that this characteristic affects the adoption of cloud ERP systems due to an organization being able to test the performance before adopting and deciding to purchase the system.…”
Section: Discussionmentioning
confidence: 99%
“…It significantly affects technology adoption in SMEs. As technology adoption can be riskier for SMEs with limited ICT support (Low et al, 2022), innovative SMEs are more likely to embrace such a risky solution (Opasvitayarux et al, 2022;Nazir et al, 2023). Organizational innovation plays a crucial role in influencing the adoption of technologies (Siamagka et al, 2015).…”
Section: Organizational Contextmentioning
confidence: 99%
“…As a result, managers with IT knowledge and skills can reduce the degree of uncertainty entangled with technology adoption (Ghobakhloo et al, 2011). The ability of managers in IT knowledge and skills increases the possibility of technology adoption in SMEs (Opasvitayarux et al, 2022). Managers' IT knowledge is the most critical determinant for technology adoption in SMEs (Nair et al, 2019;Singh et al, 2021;Henao-Ramı ´rez and L opez-Zapata, 2022).…”
Section: Managerial Contextmentioning
confidence: 99%
“…IoT in general enables more efficient information gathering and communication between employees and potentially hazardous workplace conditions, resulting in more dynamic risk analysis [1]. Moreover, IIoT is expected to play a key role in not only the industrial paradigm shift but also future management change [21]. In the field of safety, the IoT offers a comprehensive set of technologies for monitoring and controlling the manufacturing environment at its source.…”
Section: Internet Of Things (Iot) and Industrial Internet Of Things (...mentioning
confidence: 99%
“…The literatures on IoT or IIoT are abundant as scholars are attempting to uncover the many technologies associated with it [8], drivers [25], barriers, and challenges [14], and benefits of its adoption [15] in various industries. For example, the topic of IoT is vastly studied in construction industry [7], food safety [21] and cold supply chain [29]. Scholars in general were focusing on the operational efficiency gain, improved visibility, and cost-effective approaches for business owners to adopt IoT.…”
Section: Research Gapmentioning
confidence: 99%